Specific tackling situations affect the biomechanical demands experienced by rugby union players. Issue 1 (2nd January 2017) - Seminati, Elena; Cazzola, Dario; Preatoni, Ezio; Trewartha, Grant
Abstract: Tackling in Rugby Union is an open skill which can involve high-speed collisions and is the match event associated with the greatest proportion of injuries. This study aimed to analyse the biomechanics of rugby tackling under three conditions: from a stationary position, with dominant and non-dominant shoulder, and moving forward, with dominant shoulder. A specially devised contact simulator, a 50-kg punch bag instrumented with pressure sensors, was translated towards the tackler ( n  = 15) to evaluate the effect of laterality and tackling approach on the external loads absorbed by the tackler, on head and trunk motion, and on trunk muscle activities. Peak impact force was substantially higher in the stationary dominant (2.84 ± 0.74 kN) than in the stationary non-dominant condition (2.44 ± 0.64 kN), but lower than in the moving condition (3.40 ± 0.86 kN). Muscle activation started on average 300 ms before impact, with higher activation for impact-side trapezius and non-impact-side erector spinae and gluteus maximus muscles. Players' technique for non-dominant-side tackles was less compliant with current coaching recommendations in terms of cervical motion (more neck flexion and lateral bending in the stationary non-dominant condition) and players could benefit from specific coaching focus on non-dominant-side tackles.